Accepting the pressures of coaching: insights into what coaches learn with over 10 years of experience working with elite junior tennis players - Gowling, C. (Coaching and Sport Science Review, 2020)
Despite a growing body of research into sports coaching there is little understanding of what it is like to coach elite junior tennis players. The purpose of this study was to examine the experiences of 8 UK, experienced tennis coaches and describe what it is like to coach elite junior tennis players. An Interpretative Phenomenological Analysis (IPA) of 8 experienced tennis coaches (over 10 years-experience) shows their insights into elite junior tennis coaching and provides avenues of comparison with the experiences of younger tennis coaches (Gowling, 2019). This study found that (a) experienced tennis coaches described a panoramic view of coaching, (b) experienced coaches were confident in their coaching effectiveness, and (c) acceptance of challenges in coaching helped experienced coaches develop effective coping mechanisms to sustain their emotional well-being and motivation to coach for long careers. The findings of this research contribute to an evolving, problematic epistemology of sports coaching and confirms that the experiences of existing coaches could contribute to more effective training of coaches. The findings present governing bodies opportunities to inform coach education literature and help tennis coaches to sustain themselves in an emotionally challenging role